The Challenges of Integrating Behavioral and Neural Data: Bridging and Breaking Boundaries Across Levels of Analysis - Ortu, Daniele (Behav Anal, 2016)
We describe here two approaches introduced by Abrahamsen (1987) that can be used by behavior analysts to interpret neuroscientific data. The first is a “boundary-bridging” approach aimed at understanding the interdisciplinary interactions between the behavioral and the neural levels of analysis while keeping the two domains independent. When presenting the boundary-bridging approach, we describe neuroplasticity, a perspective that describes how changes at the brain level can be understood by examining behavioral factors. In the second part of the paper, we contrast two “boundary-breaking” perspectives: neuropsychology and behavior analytic neuroscience. In neuropsychology, localized brain activation is used to explain behavior. In behavior analytic neuroscience, brain responses are interpreted as behavior. We discuss the conditions under which brain responses can be considered behavior and propose that including brain responses within a behavioral framework may allow carrying out a more sophisticated and temporally detailed behavior analysis.